THE HISTORY OF THE RELATIONS OF AFRICAN COUNTRIES WITH THE UZBEKISTAN SSR - Bobokulov Okhunjon Akhmatovich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article discusses the policy of developed countries in the process of Congo's independence and Uzbekistan's diplomatic relations with the SSR, following the feelings of friendship and brotherhood towards the Congolese people and helping them with food products